2017
DOI: 10.1021/acsami.7b02259
|View full text |Cite
|
Sign up to set email alerts
|

Thermally and Electrically Triggered Triple-Shape Memory Behavior of Poly(vinyl acetate)/Poly(lactic acid) Due to Graphene-Induced Phase Separation

Abstract: This work aimed to develop a facile and broadly applicable method for fabricating multistimuli responsive triple-shape memory polymers (SMPs). Hence, herein the SMPs were prepared through the simple physical blending of two commercially available biopolymers, poly(lactic acid) (PLA) and poly(vinyl acetate) (PVAc), in the presence of robust and conductive graphene nanoplatelets. Interestingly, atomic force microscopy observations and thermal analyses revealed that the presence of nanofillers led to phase separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…While, the samples containing graphene have an excellent shape recovery behavior, as the R r (C → A) value for PLA‐G/PVAc‐G reached to 99.6% [Figure (d)]. These results are consistent with our previous observations that revealed excellent thermally actuated triple‐SM properties of the PLA/PVAc/graphene nanocomposite fabricated through solution blending method . Moreover, the R r (C → B) value of PLA/PVAc‐G is over 100%.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…While, the samples containing graphene have an excellent shape recovery behavior, as the R r (C → A) value for PLA‐G/PVAc‐G reached to 99.6% [Figure (d)]. These results are consistent with our previous observations that revealed excellent thermally actuated triple‐SM properties of the PLA/PVAc/graphene nanocomposite fabricated through solution blending method . Moreover, the R r (C → B) value of PLA/PVAc‐G is over 100%.…”
Section: Resultssupporting
confidence: 90%
“…Additionally, it can be seen from Figure (b) and Table that embedding of graphene into the PLA and PVAc matrices led to a considerable reduction in the intensity (tan δ max ) and area of the loss factor peak of PLA, implying that less amount of energy can be dissipated during the deformation process and, as a result, more elastic energy can be stored in graphene‐loaded nanocomposite samples …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The shape fixation ratio determines the ability of the switch segment to be deformed or temporarily shaped. The shape recovery ratio determines the competence of the material to remember permanent shapes . As we can see from the figure, the fixed rate of neat PLA and its composite material was about 90%, which was not changed by the addition of H‐PLA‐CNCs.…”
Section: Resultsmentioning
confidence: 94%
“…From the viewpoint of applications, electroactive SMPI (EASMPI) that can be activated conveniently with electricity is strongly desired, but the SMPIs reported are just activated with direct heat until now . During the exploration, we have observed that it is very difficult for some conductive fillers such as silver nanowires, carbon nanotubes, carbon black, and graphene to produce EASMPI, although they have produced other electroactive SMPs . Short carbon fiber is an attractive candidate for EASMPI, as it exhibits advantages including lower density than metal fibers, higher conductivity than carbon nanotubes, and less amount to form conductive network than carbon black and graphenes .…”
Section: Introductionmentioning
confidence: 99%